Towards a Model for Integrating Process Verification in Process-Driven Application Development - Nguyen, Thanh Tuan (The University of Danang - Journal of Science and Technology (UD-JST), 2025)
The University of Danang - Journal of Science and Technology (UD-JST); Vol.22, No.11A, 2024; pp: 59-64.